Migrating to iPhone and iPad for .NET Developers - Mamone, Mark (Apress, 2011)
Today's .NET developers are intrigued by what the iPhone and iPad apps landscape has to offer. Admit it: you're one of them. Apple's App Store has hundreds of thousands of apps, and yours can be among them. iPhone and iPad app development using the iOS software development kit is one of the most appealing environments available for mobile technology. Migrating to iPhone and iPad for .NET Developers helps .NET programmers get started creating iPhone and iPad apps using the iOS software development kit. Start with a crash course on development using iOS. Then, find out whether you want to use Xcode instead of Visual Studio, and prepare yourself for the migration from C# to Objective-C! You'll learn how your existing .NET skills can map most efficiently to the iOS development environment. Next, you'll really get coding with Objective-C and the iOS software development kit. You'll build your skills and enhance your apps with visually appealing, dynamic user interfaces and pushing/pulling data from a database though events and more. Discover the wonders of the Cocoa library, and learn new ways to do things you already know like the back of your hand in the .NET environment. Nearing the finish line, you'll build your first complete iPhone or iPad app, and extend your iPhone app features for example, by using third-party libraries. Once you have created that first iPhone or iPad app, we'll walk you through making it available on the App Store. Migrating to iPhone and iPad for .NET Developers even offers tips on how to market your apps to new customers. When you finish reading Migrating to iPhone and iPad for .NET Developers, you'll be an iOS apps developer as well as a .NET developer, in today's competitive and fun mobile landscape!